2004
DOI: 10.1096/fj.03-0545fje
|View full text |Cite
|
Sign up to set email alerts
|

Versican/PG‐M G3 domain promotes tumor growth and angiogenesis

Abstract: Versican/PG-M is an extracellular matrix proteoglycan, expression of which is elevated in a variety of human tumors. The significance of this change is unclear. Here we show that versican G3-containing fragments are present at high levels in human astrocytoma. Expression of a versican G3 construct in U87 astrocytoma cells enhances colony growth in soft agarose gel and tumor growth and blood vessel formation in nude mice. The G3-containing medium enhances endothelial cell adhesion, proliferation, and migration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
136
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 46 publications
11
136
0
3
Order By: Relevance
“…Previously, the versican G3 domain was found to be important in astrocytoma cell proliferation, glioma adhesion, tumour growth and angiogenesis (Wu et al, 2002(Wu et al, , 2004aZheng et al, 2004). Our results indicate that the V0/V1 isoforms modulate glioma migration through their common GAGb-domain.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previously, the versican G3 domain was found to be important in astrocytoma cell proliferation, glioma adhesion, tumour growth and angiogenesis (Wu et al, 2002(Wu et al, , 2004aZheng et al, 2004). Our results indicate that the V0/V1 isoforms modulate glioma migration through their common GAGb-domain.…”
Section: Discussionsupporting
confidence: 54%
“…Cleavage of brevican, another member of the lectican family by ADAMTS-5 is functionally involved in glioma invasion in vivo (Nakada et al, 2005). There is a strong likelihood that breakdown products of versican will also have biological activity in glioma probably paving the way for the invasion into tissue (Zheng et al, 2004). However, it is not entirely clear if proteolytic degradation of versican by MMP-2 and ADAMTS-1 and 4 induced by TGF-b2 has a pathophysiological role in glioma progression.…”
Section: Discussionmentioning
confidence: 99%
“…46 In PyMT ϩ mammary tumors, the apoptotic index was lower in Adamts1 ϩ/ϩ than in Adamts1 Ϫ/Ϫ tumors, despite equivalent vascular density and cleaved versican accumulated in peritumoral stroma. The liberated G3 domain of cleaved versican has EGF-like activity [47][48][49] and might act as an EGF-like signal in the Adamts1 ϩ/ϩ tumor microenvironment, resulting in reduced apoptosis and increased tumor growth compared with null littermates.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that versican G3 domain enhances tumor growth and angiogenesis, perhaps through enhancement of fibronectin expression [71]. We then investigated the possibility that the G3 domain interacts with fibronectin.…”
Section: Versican Interaction With Fibronectinmentioning
confidence: 99%